Legal Culture Obligation to Submit Tax Data and Information from Agencies, Institutions, Associations, and Other Parties - Maryano, Maryano; Natalius, Natalius; Anggraeni, RR Dewi (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
Law Number 28 of 2007 and Government Regulation Number 31 of 2012 mandate the provision of tax data by government agencies, institutions, associations and other parties (ILAP) to the Directorate General of Taxes (DJP). Even though criminal sanctions have been regulated, the implementation of these obligations is not optimal. DJP adopted alternative methods, such as a Memorandum of Understanding/MoU, to obtain tax data from ILAP. This research uses a research method that focuses on positive law with the theory of legal certainty by Gustav Radbruch, the theory of authority by Max Weber, and the theory of taxation by Adam Smith. The results of the research show that there is a discrepancy in the implementation of the obligation to submit tax data with positive law and the theory of legal certainty. Steps are needed to create a Memorandum of Understanding/Agreement/MoU up to a Cooperation Agreement by the DJP with ILAP to make the obligation to submit tax data and information from ILAP run smoothly in accordance with the study. theory of authority by Max Weber. To realize legal certainty in these regulations and to increase state revenues in accordance with the study of tax theory by Adam Smith, it is recommended that there be changes to norms in Law Number 28 of 2007 by adding an article regarding the making of a Memorandum of Understanding/MoU/Cooperation Agreement to increase legal certainty. and contribution to state revenue.Keywords: Reconstruction of Obligations; Data Submission; Tax Information; Legal certainty